The host response: adaptive immune response to viral vector delivery - Herzog, Roland W. (Henry Stewart Talks, 2014)
Gene therapy using viral vector, Risk of immune responses specific to vector or transgene product, Pre-existing immunity to viral vectors due to natural infection, Design of vectors to minimize or entirely avoid B and T cell responses, Modification of gene transfer protocols to minimize/avoid/circumvent B and T cell responses